Seeking Zion : modernity and messianic activism in the writings of Tsevi Hirsch Kalischer - Myers, Jody Elizabeth, 1954- (Littman library of Jewish civilization (Series), 2012)
Focusing on the teachings of Tsevi Hirsch Kalischer, this study examines the modern revival of the belief among religious Jews that they are duty-bound to hasten messianic redemption.